Pengembangan Buku Ajar Program Linier pada Mahasiswa Pendidikan Matematika - Fitriana Yolanda; Putri Wahyuni (SJME (Supremum Journal of Mathematics Education), 2022)
This study aims to develop a Linear Program textbook for Mathematics Education students. This research is a research and development research that begins with potential and problem steps, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision and mass production. The research carried out only reached the step of knowing the validity of the Linear Program textbooks that had been developed. The instrument used is a learning expert validation sheet. The data analysis technique used is descriptive statistical analysis. This research was conducted on second semester students of Mathematics Education FKIP Riau Islamic University in the Linear Program course. This research was conducted in the 2020/2021 Academic year. From the results of the study, it was obtained that the overall percentage average for each aspect of the validation sheet assessment was 85.4% with Very Valid criteria. The Linear Program textbook that has been developed can be called valid because it has met three aspects of the textbook validation criteria, namely aspects, namely Aspects of Content (content), Aspects of Construct (presentation) and Aspects of Language. Therefore, it can be concluded that the Linear Program textbook has been tested for validity, so that it can be used in the learning process.